A method for preparing copper-doped prussian blue-silica nanoparticles

CN122706171BActive Publication Date: 2026-10-30PENGLAI XINGUANG PIGMENT CHEM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611191231.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-30
Estimated Expiration
2046-08-07

AI Technical Summary

Technical Problem

然而,现有附着普鲁士蓝的复合材料的制备工艺较为复杂,普遍存在下述技术瓶颈:普鲁士蓝与基底材料(如无机氧化物、高分子等)之间的界面结合力较弱,导致普鲁士蓝的附着力差,易于从基底材料上脱落,无法充分发挥其性能优势

Benefits of technology

本发明掺杂铜的普鲁士蓝-二氧化硅纳米颗粒,稳定性和附着力优异。本发明的制备方法,采用溶胶凝胶法制备了二氧化硅粉末,然后通过氢键作用在其表面包裹羧甲基壳聚糖,得到羧甲基壳聚糖改性二氧化硅,该材料与普鲁士蓝纳米颗粒混合后,普鲁士蓝均匀附着在二氧化硅表面,进一步进行煅烧后,羧甲基壳聚糖碳化,形成碳层,一侧与二氧化硅表面的硅羟基(Si-OH)形成牢固的共价键(如Si-O-C)或强烈的物理吸附;另一侧与掺杂铜的普鲁士蓝纳米粒表面的铁原子等形成Fe-O-C等化学键或强配位作用,如同无数个分子锚点,将掺杂铜的普鲁士蓝纳米粒壳层牢牢绑定在二氧化硅核心上,稳定性和附着力好。此外,煅烧过程中还加入了铜粉,能够“撑开”并稳定普鲁士蓝的骨架结构,形成稳定的铜-铁氰桥配合物,大幅减少晶格缺陷,使所得复合材料的结构更稳定,不易分解或脱色。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122706171B_ABST
    Figure CN122706171B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of copper-doped Prussian blue-silica nanoparticles and relates to the technical field of Prussian blue nanomaterials. The application adopts a sol-gel method to prepare silica powder, then wraps carboxymethyl chitosan on the surface of the silica powder through hydrogen bond action to obtain carboxymethyl chitosan modified silica. After the material is mixed with Prussian blue nanoparticles, the Prussian blue is uniformly attached to the surface of the silica. After further calcination, the carboxymethyl chitosan is carbonized to form a carbon layer, one side of which forms a firm covalent bond or strong physical adsorption with the silicon hydroxyl groups on the surface of the silica. The other side forms Fe-O-C chemical bonds or strong coordination action with iron atoms on the surface of the copper-doped Prussian blue nanoparticles, like countless molecular anchor points, which firmly bind the shell of the copper-doped Prussian blue nanoparticles to the silica core, and the stability and adhesion are good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of Prussian blue nanomaterials technology, specifically to a method for preparing copper-doped Prussian blue-silica nanoparticles. Background Technology

[0002] Prussian blue, a classic organometallic compound, has a long history of application in the pigment and dye industry. Due to its unique octahedral structure, Prussian blue exhibits excellent optical properties and is widely used. However, Prussian blue generally has poor stability. When exposed to external environmental factors (such as light, temperature, and humidity changes) for extended periods, or when dyeing certain special papers or fabrics, it is prone to discoloration or aggregation, which severely affects its final dyeing effect and lifespan.

[0003] Attaching Prussian blue to various substrate materials is an effective strategy to improve its stability and dispersibility during the coloring process. By forming composite materials, the aggregation of Prussian blue nanoparticles can be suppressed and its resistance to the external environment enhanced by the support and protection provided by the substrate material. However, existing processes for preparing Prussian blue-attached composite materials are relatively complex and generally suffer from the following technical bottlenecks: the interfacial bonding between Prussian blue and the substrate material (such as inorganic oxides, polymers, etc.) is weak, resulting in poor adhesion of Prussian blue, making it easy for it to detach from the substrate material and thus failing to fully realize its performance advantages.

[0004] Therefore, how to prepare a Prussian blue composite material with excellent stability through a simple and easy-to-operate process, and achieve a strong bond between Prussian blue and the substrate, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to provide a method for preparing copper-doped Prussian blue-silica nanoparticles.

[0006] To achieve the above objectives, the present invention employs the following technical solution: A method for preparing copper-doped Prussian blue-silica nanoparticles includes the following steps: ① By weight, add 3-5 parts of ammonia water to 80-85 parts of ethanol with a mass concentration of 90-95%, heat to 35-40℃, and add 10-15 parts of tetraethyl orthosilicate dropwise while stirring. After the addition is complete, continue stirring for 2-4 hours, centrifuge, wash the resulting precipitate with ethanol until the pH value is <7.3, add it to 55-65 parts of carboxymethyl chitosan aqueous solution with a mass concentration of 1-3%, stir for 6-10 hours, centrifuge, wash the resulting precipitate with ethanol, and dry to obtain carboxymethyl chitosan modified silica; ② Add 40-60 parts of polyvinylpyrrolidone to 450-550 parts of deionized water, stir for 5-15 minutes, add 3.5-4 parts of potassium ferrocyanide and 150-200 parts of hydrochloric acid aqueous solution, heat the mixture to 75-85℃, stir and react for 10-16 hours, centrifuge, and wash the precipitate with water to obtain Prussian blue nanoparticles. ③ Take 6-7 parts of the carboxymethyl chitosan-modified silica obtained in step ①, 2.8-3.2 parts of the Prussian blue nanoparticles obtained in step ②, and 0.1-0.15 parts of copper powder, disperse them in 55-60 parts of ethanol with a mass concentration of 90-95%, stir for 30-60 minutes, centrifuge, dry the resulting solid, add it to a quartz glass tube, seal it after vacuuming, place it in a muffle furnace, heat it to 300-310℃, calcine it for 1-2 hours, and cool it to 20-30℃ to obtain copper-doped Prussian blue-silica nanoparticles.

[0007] Preferably, the dropping rate of tetraethyl orthosilicate is 1~2 ml / min.

[0008] Preferably, the molar concentration of the hydrochloric acid aqueous solution is 0.02~0.05 mol / L.

[0009] Preferably, the mass concentration of the ammonia water is 20-22%.

[0010] Preferably, the degree of carboxylation of the carboxymethyl chitosan is 80-90%.

[0011] Preferably, the centrifugation speed in step ② is 10000~12000 rpm.

[0012] Preferably, the heating rate of the muffle furnace is 5~10℃ / minute.

[0013] The copper-doped Prussian blue-silica nanoparticles obtained by the above preparation method have a double core-shell structure. The core layer is silica microspheres, and the shell layer is copper-doped Prussian blue nanoparticles (copper powder was also added during the calcination process, so the shell layer is doped with copper). The silica microspheres have a carbon layer formed by calcination of carboxymethyl chitosan. The carbon layer is highly dispersed and generated in situ on the surface of the silica microspheres. The other side of the carbon layer is connected to the copper-doped Prussian blue nanoparticles.

[0014] The present invention has the following advantages over the prior art: This invention relates to copper-doped Prussian blue-silica nanoparticles, which exhibit excellent stability and adhesion. The preparation method involves using a sol-gel method to prepare silica powder, followed by encapsulation of carboxymethyl chitosan on its surface via hydrogen bonding, resulting in carboxymethyl chitosan-modified silica. When this material is mixed with Prussian blue nanoparticles, the Prussian blue adheres uniformly to the silica surface. Further calcination carbonizes the carboxymethyl chitosan, forming a carbon layer. On one side, this carbon layer forms strong covalent bonds (such as Si-OC) or strong physical adsorption with the silanol groups (Si-OH) on the silica surface; on the other side, it forms chemical bonds such as Fe-OC or strong coordination with iron atoms on the surface of the copper-doped Prussian blue nanoparticles. These numerous molecular anchors firmly bind the shell of the copper-doped Prussian blue nanoparticles to the silica core, resulting in excellent stability and adhesion. In addition, copper powder is added during the calcination process, which can "stretch" and stabilize the framework structure of Prussian blue, forming a stable copper-ferric cyanide bridge complex, greatly reducing lattice defects, making the resulting composite material more stable and less prone to decomposition or discoloration. Attached Figure Description

[0015] Figure 1 This is a comparison diagram of the dispersibility of copper-doped Prussian blue-silica nanoparticles prepared in Example 5 of the present invention with commercially available Prussian blue. Figure 2 Images of existing Prussian blue products before accelerated aging tests; Figure 3 Images of existing Prussian blue products after accelerated aging tests; Figure 4 This is a picture of the copper-doped Prussian blue-silica nanoparticles obtained in Example 5 before the accelerated aging test. Figure 5 This is an image taken 1000 hours after accelerated aging of the copper-doped Prussian blue-silica nanoparticles obtained in Example 5. Figure 6 This is an image taken 1500 hours after an accelerated aging test of the copper-doped Prussian blue-silica nanoparticles obtained in Example 5. Detailed Implementation

[0016] The purpose of this invention is to provide a method for preparing copper-doped Prussian blue-silica nanoparticles. The invention will be further described below with reference to specific embodiments.

[0017] The vacuum sealing operation of the present invention can be performed using a vacuum pump, a vacuum sealing machine, and a backfire-proof flame gun. This includes heating the quartz to a softened state with a flame, stretching it into a gourd shape, and then sealing the gourd shape with a flame after vacuuming. Alternatively, an oxyhydrogen flame quartz glass tube sealing machine can be used.

[0018] Example 1: A method for preparing copper-doped Prussian blue-silica nanoparticles, comprising the following steps: ① Add 30g of 20% ammonia solution to 800g of 90% ethanol, heat to 35℃, and add 100g of tetraethyl orthosilicate dropwise while stirring. After the addition is complete, continue stirring for 2 hours, centrifuge, wash the resulting precipitate with ethanol until the pH value is <7.3, add it to 550g of 1% carboxymethyl chitosan aqueous solution, stir for 6 hours, centrifuge, wash the resulting precipitate with ethanol, and dry to obtain carboxymethyl chitosan modified silica; the dropping rate of tetraethyl orthosilicate is 1ml / min; the degree of carboxylation of the carboxymethyl chitosan is 80%; ② Add 400g of polyvinylpyrrolidone to 4.5kg of deionized water and stir for 5 minutes. Add 35g of potassium ferrocyanide and 1.5kg of hydrochloric acid solution. Heat the mixture to 75℃ and stir for 10 hours. Centrifuge at 10000rpm and wash the precipitate with water to obtain Prussian blue nanoparticles. The molar concentration of the hydrochloric acid aqueous solution is 0.02 mol / L; ③ Take 60g of carboxymethyl chitosan-modified silica obtained in step ①, 28g of Prussian blue nanoparticles obtained in step ②, and 1g of copper powder, disperse them in 550g of 90% ethanol, stir for 30 minutes, centrifuge, dry the resulting solid, add it to a quartz glass tube, evacuate and seal it, place it in a muffle furnace, heat it to 300℃ at a rate of 5℃ / min, calcine it for 1 hour, cool it to 20℃, and obtain copper-doped Prussian blue-silica nanoparticles.

[0019] Example 2: A method for preparing copper-doped Prussian blue-silica nanoparticles, comprising the following steps: ① Add 50g of 22% ammonia solution to 850g of 95% ethanol, heat to 40℃, and add 150g of tetraethyl orthosilicate dropwise while stirring. After the addition is complete, continue stirring for 4 hours, centrifuge, wash the resulting precipitate with ethanol until the pH value is <7.3, add it to 650g of 3% carboxymethyl chitosan aqueous solution, stir for 10 hours, centrifuge, wash the resulting precipitate with ethanol, and dry to obtain carboxymethyl chitosan modified silica; the dropping rate of tetraethyl orthosilicate is 2ml / min; the degree of carboxylation of the carboxymethyl chitosan is 90%. ② Add 600g of polyvinylpyrrolidone to 5.5kg of deionized water and stir for 15 minutes. Add 40g of potassium ferrocyanide and 2kg of hydrochloric acid solution. Heat the mixture to 85℃ and stir for 16 hours. Centrifuge at 12000rpm and wash the precipitate with water to obtain Prussian blue nanoparticles. The molar concentration of the hydrochloric acid aqueous solution is 0.05 mol / L; ③ Take 70g of carboxymethyl chitosan-modified silica obtained in step ①, 32g of Prussian blue nanoparticles obtained in step ②, and 1.5g of copper powder, disperse them in 600g of 95% ethanol, stir for 60 minutes, centrifuge, dry the resulting solid, add it to a quartz glass tube, seal it after vacuuming, place it in a muffle furnace, heat it to 310℃ at a rate of 10℃ / min, calcine it for 2 hours, cool it to 30℃, and obtain copper-doped Prussian blue-silica nanoparticles.

[0020] Example 3: A method for preparing copper-doped Prussian blue-silica nanoparticles, comprising the following steps: ① Add 35g of 21% ammonia solution to 820g of 92% ethanol, heat to 36℃, and add 120g of tetraethyl orthosilicate dropwise while stirring. After the addition is complete, continue stirring for 2.5 hours, centrifuge, and wash the resulting precipitate with ethanol until the pH value is <7.3. Add the precipitate to 560g of 1.5% carboxymethyl chitosan aqueous solution, stir for 7 hours, centrifuge, wash the resulting precipitate with ethanol, and dry to obtain carboxymethyl chitosan modified silica; the dropping rate of tetraethyl orthosilicate is 1.5ml / min; the degree of carboxylation of the carboxymethyl chitosan is 85%. ② Add 500g of polyvinylpyrrolidone to 4.6kg of deionized water and stir for 8 minutes. Add 36g of potassium ferrocyanide and 1.6kg of hydrochloric acid aqueous solution. Heat the mixture to 78℃ and stir for 12 hours. Centrifuge at 11000rpm and wash the precipitate with water to obtain Prussian blue nanoparticles. The molar concentration of the hydrochloric acid aqueous solution is 0.03 mol / L; ③ Take 65g of carboxymethyl chitosan-modified silica obtained in step ①, 29g of Prussian blue nanoparticles obtained in step ②, and 1.2g of copper powder, disperse them in 560g of 92% ethanol, stir for 40 minutes, centrifuge, dry the resulting solid, add it to a quartz glass tube, seal it after vacuuming, place it in a muffle furnace, heat it to 302℃ at a rate of 6℃ / min, calcine it for 1.5 hours, cool it to 22℃, and obtain copper-doped Prussian blue-silica nanoparticles.

[0021] Example 4: A method for preparing copper-doped Prussian blue-silica nanoparticles, comprising the following steps: ① Add 45g of 21.5% ammonia solution to 840g of 91% ethanol, heat to 38℃, and add 140g of tetraethyl orthosilicate dropwise while stirring. After the addition is complete, continue stirring for 3.5 hours, centrifuge, wash the resulting precipitate with ethanol until the pH value is <7.3, add it to 620g of 2.5% carboxymethyl chitosan aqueous solution, stir for 7 hours, centrifuge, wash the resulting precipitate with ethanol, and dry to obtain carboxymethyl chitosan modified silica; the dropping rate of tetraethyl orthosilicate is 1.8ml / min; the degree of carboxylation of the carboxymethyl chitosan is 86%. ② Add 550g of polyvinylpyrrolidone to 5.2kg of deionized water and stir for 12 minutes. Add 38g of potassium ferrocyanide and 1.8kg of hydrochloric acid aqueous solution. Heat the mixture to 82℃ and stir for 15 hours. Centrifuge at 10500rpm and wash the precipitate with water to obtain Prussian blue nanoparticles. The molar concentration of the hydrochloric acid aqueous solution is 0.04 mol / L; ③ Take 65g of carboxymethyl chitosan-modified silica obtained in step ①, 30g of Prussian blue nanoparticles obtained in step ②, and 1.4g of copper powder, disperse them in 580g of 92% ethanol, stir for 50 minutes, centrifuge, dry the resulting solid, add it to a quartz glass tube, evacuate and seal it, place it in a muffle furnace, heat it to 305℃ at a rate of 8℃ / min, calcine it for 1.5 hours, cool it to 25℃, and obtain copper-doped Prussian blue-silica nanoparticles.

[0022] Example 5: A method for preparing copper-doped Prussian blue-silica nanoparticles, comprising the following steps: ① Add 40g of 21% ammonia solution to 840g of 92% ethanol, heat to 38℃, and add 120g of tetraethyl orthosilicate dropwise while stirring. After the addition is complete, continue stirring for 3 hours, centrifuge, wash the resulting precipitate with ethanol until the pH value is <7.3, add it to 600g of 2% carboxymethyl chitosan aqueous solution, stir for 8 hours, centrifuge, wash the resulting precipitate with ethanol, and dry to obtain carboxymethyl chitosan modified silica; the dropping rate of tetraethyl orthosilicate is 1.5ml / min; the degree of carboxylation of the carboxymethyl chitosan is 85%. ② Add 500g of polyvinylpyrrolidone to 5kg of deionized water and stir for 10 minutes. Add 38g of potassium ferrocyanide and 1.8kg of hydrochloric acid solution. Heat the mixture to 80℃ and stir for 15 hours. Centrifuge at 11000rpm and wash the precipitate with water to obtain Prussian blue nanoparticles. The molar concentration of the hydrochloric acid aqueous solution is 0.03 mol / L; ③ Take 65g of carboxymethyl chitosan-modified silica obtained in step ①, 30g of Prussian blue nanoparticles obtained in step ②, and 1.2g of copper powder, disperse them in 580g of 92% ethanol, stir for 45 minutes, centrifuge, dry the resulting solid, add it to a quartz glass tube, evacuate and seal it, place it in a muffle furnace, heat it to 305℃ at a rate of 8℃ / min, calcine it for 1.5 hours, cool it to 25℃, and obtain copper-doped Prussian blue-silica nanoparticles.

[0023] One g each of the copper-doped Prussian blue-silica nanoparticles obtained in Examples 1-5 and the existing Prussian blue product (Runba Prussian blue pigment G5030) were subjected to accelerated aging tests under conditions of 5000 lux of light, 40°C, and 70% humidity. The color change of the existing Prussian blue product before and after 1000 hours of aging is shown below. Figure 2 and Figure 3 As shown, the pigments faded significantly; taking the nanoparticles of Example 5 as an example, the color changes were tested before and after aging for 1000h and 1500h as follows. Figures 4-6 As shown, the Prussian blue-silica nanoparticles of the present invention exhibit minimal fading and excellent stability.

[0024] The copper-doped Prussian blue-silica nanoparticles obtained in Examples 1-5 were tested using the following methods: GB / T 1864 General Test Methods for Pigments and Extenders - Comparison of Pigment Colors; GB / T 5211.1 Determination of Water-Soluble Matter in Pigments: Cold Extraction Method; GB / T 5211.3-2020 General Test Methods for Pigments and Extenders, Part 3: Determination of Volatile Matter at 105℃; GB / T 5211.6 General Test Methods for Pigments and Extenders, Part 6: Determination of pH Value of Aqueous Suspensions; GB / T 5211.12 Determination of Resistivity of Aqueous Extracts of Pigments; The results are shown in Table 1.

[0025] Table 1. Detection results of copper-doped Prussian blue-silica nanoparticles obtained in Examples 1-5

[0026] As can be seen from the results in Table 1, the detection parameters of the copper-doped Prussian blue-silica nanoparticles of the present invention are moderate and meet the market requirements for Prussian blue pigments.

[0027] Performance testing: The packing density of the copper-doped Prussian blue-silica nanoparticles obtained in Examples 1-5 was tested according to the method in GB / T 21877-2015. 50g of pigment compound was accurately weighed, placed in a graduated cylinder, sealed, and shaken up and down 10 times. The sample graduations in the graduated cylinder were recorded. Adhesion was tested according to the cross-cut adhesion test. Water resistance, oil resistance, acid resistance, and alkali resistance were tested according to GB 5211.5-2008, with the best result being grade 5 and the worst grade being grade 1. Commercially available Prussian blue (Runba Prussian blue pigment G5030) was used as a comparative example. The test results are shown in Table 2.

[0028] Table 2 Performance evaluation of copper-doped Prussian blue-silica nanoparticles obtained in Examples 1-5

[0029] As can be seen from the results in Table 2, the copper-doped Prussian blue-silica nanoparticles of this application have a low packing density, good dispersibility, and excellent adhesion, water resistance, and oil resistance. In particular, in terms of acid and alkali resistance, the existing commercially available Prussian blue has poor acid and alkali resistance, while the copper-doped Prussian blue-silica nanoparticles of this application can significantly improve the acid and alkali resistance of Prussian blue and have excellent stability.

[0030] To verify the dispersion performance of the copper-doped Prussian blue-silica nanoparticles prepared in this invention in water, 15g of the copper-doped Prussian blue-silica nanoparticles prepared in Example 5, 0.5g of BYK-110 dispersant, and 50g of water were mixed and ground at 2000 r / min. During the grinding process, the fineness change of the pigment was measured using a scraper fineness meter at different grinding times. Commercially available Prussian blue was used as a comparative example. The test results are as follows: Figure 1 As shown. By Figure 1 The results show that the copper-doped Prussian blue-silica nanoparticles prepared by this invention can stabilize and reach a smaller fineness in about 40 minutes compared to commercially available Prussian blue, while commercially available Prussian blue has a larger final fineness and requires a longer dispersion time. This indicates that the pigment prepared by this invention is easier to disperse in water than commercially available pigments and has great application value.

Claims

1. A method for preparing copper-doped Prussian blue-silica nanoparticles, characterized in that: Includes the following steps: ① By weight, add 3-5 parts of ammonia water to 80-85 parts of ethanol with a mass concentration of 90-95%, heat to 35-40℃, and add 10-15 parts of tetraethyl orthosilicate dropwise while stirring. After the addition is complete, continue stirring for 2-4 hours, centrifuge, wash the resulting precipitate with ethanol until the pH value is <7.3, add it to 55-65 parts of carboxymethyl chitosan aqueous solution with a mass concentration of 1-3%, stir for 6-10 hours, centrifuge, wash the resulting precipitate with ethanol, and dry to obtain carboxymethyl chitosan modified silica; The degree of carboxylation of the carboxymethyl chitosan is 80-90%. ② Add 40-60 parts of polyvinylpyrrolidone to 450-550 parts of deionized water, stir for 5-15 minutes, add 3.5-4 parts of potassium ferrocyanide and 150-200 parts of hydrochloric acid aqueous solution, heat the mixture to 75-85℃, stir and react for 10-16 hours, centrifuge, and wash the precipitate with water to obtain Prussian blue nanoparticles. ③ Take 6-7 parts of the carboxymethyl chitosan-modified silica obtained in step ①, 2.8-3.2 parts of the Prussian blue nanoparticles obtained in step ②, and 0.1-0.15 parts of copper powder, disperse them in 55-60 parts of ethanol with a mass concentration of 90-95%, stir for 30-60 minutes, centrifuge, dry the resulting solid, add it to a quartz glass tube, seal it after vacuuming, place it in a muffle furnace, heat it to 300-310℃, calcine it for 1-2 hours, and cool it to 20-30℃ to obtain copper-doped Prussian blue-silica nanoparticles.

2. The method for preparing copper-doped Prussian blue-silica nanoparticles according to claim 1, characterized in that: The dropping rate of tetraethyl orthosilicate is 1~2 ml / min.

3. The method for preparing copper-doped Prussian blue-silica nanoparticles according to claim 1, characterized in that: The molar concentration of the hydrochloric acid aqueous solution is 0.02~0.05 mol / L.

4. The method for preparing copper-doped Prussian blue-silica nanoparticles according to claim 1, characterized in that: The mass concentration of the ammonia water is 20-22%.

5. The method for preparing copper-doped Prussian blue-silica nanoparticles according to claim 1, characterized in that: The centrifugation speed in step ② is 10000~12000 rpm.

6. The method for preparing copper-doped Prussian blue-silica nanoparticles according to claim 1, characterized in that: The heating rate of the muffle furnace is 5~10℃ / minute.

Citation Information

Patent Citations

  • Hollow Prussian blue-like and mesoporous silicon dioxide composite nanometer material as well as preparation method thereof

    CN108478541A